OBTENÇÃO, CARACTERIZAÇÃO FÍSICO-QUÍMICA E AVALIAÇÃO CITOTÓXICA DE NANOPARTÍCULAS DE ALBUMINA CONTENDO DISSELENETO DE DIFENILA - LADWIG, SUELEN DAIANE (2016)
Diphenyl diselenide (DPDS) has several pharmacological properties but their physicochemical properties and toxicity limit their use. This work consisted of the obtention, physico-chemical characterization and cytotoxic activity of polymeric nanoparticles bovine serum albumin (BSA) containing DPDS obtained by desolvation method. The percentage of encapsulation of the nanoparticles was 65%, with an average diameter of 200 ± 20 nm, spherical shape and smooth surface and zeta potential of -34 ± 3mV obtained. The physicochemical characterization showed that Nanoencapsulation process resulted in an amorphous system. Through the stability study it was determined that the best nanoparticles storage condition was under refrigeration at 4°C, temperature at which the nanoparticles were stable at assessed 12 weeks with no noticeable increase in size and tend to aggregate. From the front cytotoxicity assay to red blood cells, we observed a protective effect of nanoparticles in relation to the toxicity of free DPDS. Based on the results, it was concluded that the nanostructured system containing DPDS was obtained successfully and has great potential for biological application.